Fine-root longevity of Quercus ilex - López, B; Sabate, S; Gracia, C A (New Phytologist, 2001)
* • Fine-root longevity and phenology were studied in a Quercus ilex (holm oak) forest in Prades (NE Spain). Differences were investigated among roots that had appeared in different seasons and at different depth intervals, differentiating between white and brown roots. * • Using minirhizotrons installed in March 1994, 1211 roots were monitored every 3 wk from June 1994 to March 1997. * • Mean and median fine-root longevity were 125 ± 4 d and 67 d, respectively. Longevity of summer and winter roots was greater than that of spring and autumn roots. Although roots appeared and disappeared throughout the year, the rate of appearance was greatest in spring. Maximum longevity occurred at a soil depth of 20–30 cm. Differences among 10-cm depth intervals were due to the number of days that roots were brown, since roots remained white for a similar number of days, independent of soil depth. * • Temperate soil temperatures and lignotubers permitted the appearance of roots throughout the year. Holm oak fine roots might be more efficient during the first 50 d of their life before the white roots become less efficient brown roots.
Keywords: Fine root longevity; Holm oak; minirhizotron; Quercus ilex; vertical longevity pattern

Effects of elevated CO2 and decreased water availability on holm-oak seedlings in controlled environment chambers - López, B; Sabate, S; Ruiz, I; Gracia, C (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
In Mediterranean ecosystems, water is an important limiting factor for plant growth. In addition to the increase in atmospheric CO2, some models predict increased drought in Mediterranean areas as a consequence of global change. Thus, to determine how increased atmospheric CO2 interacts with increased water stress and affects Mediterranean plant growth is an important achievement. The present study analyses how helm oak (Quercus ilex L.) seedlings are affected by both elevated CO2 and increased water stress. The CO2 concentrations were supplied in controlled environment chambers (350 and 500 ppm CO2), and water stress was performed according to a Mediterranean pattern (Potential Evapotranspiration to Rainfall ratio). The increased water stress was attained by watering half of the Mediterranean reference pattern. Results show that the positive effects of elevated CO2 on photosynthesis and growth are counteracted by increased water stress.
Keywords: CO2; controlled environment chambers; Quercus ilex